Advancing Rural Tourism in Adjara: Key Projects and Strategic Approaches - Khakhubia, Nino; Gogitidze, Giorgi; Shainidze, Jumber; Lazishvili, Sophio; Goguadze, Lela (European Scientific Journal, ESJ, 2025)
This article explores the development of rural tourism in general, the evolution of its definition, and its connection to the UN’s Sustainable Development Goals. It focuses on key projects and strategies that have driven the growth of this sector in the Adjara region. With its diverse landscapes, rich cultural heritage, and traditional agricultural practices, Adjara has become a significant destination for rural tourism. The study highlights various initiatives and community-based tourism projects supported by governmental and international organisations. The findings suggest that rural tourism offers local communities economic opportunities and contributes to cultural heritage preservation and environmental sustainability.